2021
DOI: 10.1161/circresaha.119.316547
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin3 Stabilizes McT1-Mediated Lactate/Proton Transport in Cardiomyocytes

Abstract: Rationale: Caveolin3 variants associated with arrhythmogenic cardiomyopathy and muscular dystrophy can disrupt post-Golgi surface trafficking. As Caveolin1 was recently identified in cardiomyocytes, we hypothesize that conserved isoform-specific protein/protein interactions orchestrate unique cardiomyocyte microdomain functions. To analyze the Caveolin1 versus Caveolin3 interactome, we employed unbiased live-cell proximity proteomic, isoform-specific affinity, and complexome profiling mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Early work suggested that JPH2 might associate with the atypical, partly membrane-integral and cytosolic muscle-specific caveolin-3 protein ( 111 ). Caveolin-3 functions as a cholesterol-binding multimeric scaffolding complex, which stabilizes the omega-shaped membrane invaginations known as caveolae ( 112 ). A JPH2 interaction with the cardiac Ca V 1.2-α1C channel and caveolin-3 was proposed based on cultured isolated adult rat cardiomyocyte immunostaining, proximity ligation, and confocal imaging.…”
Section: Junctophilin Biogenesis and Molecular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work suggested that JPH2 might associate with the atypical, partly membrane-integral and cytosolic muscle-specific caveolin-3 protein ( 111 ). Caveolin-3 functions as a cholesterol-binding multimeric scaffolding complex, which stabilizes the omega-shaped membrane invaginations known as caveolae ( 112 ). A JPH2 interaction with the cardiac Ca V 1.2-α1C channel and caveolin-3 was proposed based on cultured isolated adult rat cardiomyocyte immunostaining, proximity ligation, and confocal imaging.…”
Section: Junctophilin Biogenesis and Molecular Functionsmentioning
confidence: 99%
“…Proximity based ligation of the antibody-labeled JPH2 and caveolin-3 established a nanometric protein association in cultured rat cardiomyocytes ( 113 ). Smaller caveolin-3 scaffolds stabilize the function of multiple membrane transporters including the voltage-dependent cardiac Na V 1.5 channel and the monocarboxylate lactate/pyruvate shuttle McT1 in ventricular cardiomyocytes ( 112 ). Immunoprecipitation experiments confirmed multiple caveolin-3-specific transmembrane protein interactions, raising the possibility that JPH2 is additionally anchored at the cytosolic PM leaflet through direct or indirect binding to caveolin-3 scaffolds.…”
Section: Junctophilin Biogenesis and Molecular Functionsmentioning
confidence: 99%
“…Ventricular cardiomyocytes were isolated and quality controlled as described previously ( Wagner et al, 2014 ; Peper et al, 2021 ). Isolated cardiomyocyte suspensions were plated onto laminin-coated glass coverslips (Imaging Dish CG 1.0, Zellkontakt, Nörten-Hardenberg, Germany) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Since iPSCs are human in origin and pluripotent, they have enabled the development of patient-specific cell models to recapitulate the pathophysiology of human diseases [ 8 ]. This facilitates the study of inherited diseases, since the derived iPSCs and their differentiated cells will contain the same genomic profile as their patient somatic cell origin [ 31 ].…”
Section: The Advantages Of An Ipsc-based Modelmentioning
confidence: 99%
“…These cellular and electrophysiological differences may limit the usefulness of rodent models in studying X-linked cardiomyopathy [ 4 ]. With technical advancements in cellular reprogramming, adult somatic cells can now be reprogrammed into pluripotent stem cells [ 5 , 6 , 7 ], and such induced pluripotent stem cells (iPSCs) can be further differentiated into cardiomyocytes for disease modelling and drug testing [ 8 ]. To date, various studies have evaluated the possibility of using patient-specific iPSCs to model different forms of X-linked cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%